2015
DOI: 10.1186/s12967-015-0610-1
|View full text |Cite
|
Sign up to set email alerts
|

Taurine: the appeal of a safe amino acid for skeletal muscle disorders

Abstract: Taurine is a natural amino acid present as free form in many mammalian tissues and in particular in skeletal muscle. Taurine exerts many physiological functions, including membrane stabilization, osmoregulation and cytoprotective effects, antioxidant and anti-inflammatory actions as well as modulation of intracellular calcium concentration and ion channel function. In addition taurine may control muscle metabolism and gene expression, through yet unclear mechanisms. This review summarizes the effects of taurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
166
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 149 publications
(197 reference statements)
1
166
1
5
Order By: Relevance
“…A proteomic study of the heart muscle from 20-month-old mdx mice has also shown a modest yet significant 1.4-fold increase of AR protein levels. 24 In contrast to the increased expression we report here, significantly lower TauT levels have been found in mdx muscle (reviewed in De Luca et al 25 ), and taurine supplements were shown to ameliorate exercise-induced loss of muscle strength in these mice. 26 This discrepancy could reflect the unique features of human disease vs the murine disease model.…”
Section: Osmolyte Pathway Activation In Dmdcontrasting
confidence: 77%
“…A proteomic study of the heart muscle from 20-month-old mdx mice has also shown a modest yet significant 1.4-fold increase of AR protein levels. 24 In contrast to the increased expression we report here, significantly lower TauT levels have been found in mdx muscle (reviewed in De Luca et al 25 ), and taurine supplements were shown to ameliorate exercise-induced loss of muscle strength in these mice. 26 This discrepancy could reflect the unique features of human disease vs the murine disease model.…”
Section: Osmolyte Pathway Activation In Dmdcontrasting
confidence: 77%
“…Cellular biosynthesis of taurine occurs in the liver via the cysteine sulfonic acid pathway while it is exogenously obtained from dietary sources (Huxtable 1992;De Luca et al 2015). Besides its nutraceutical role, taurine reportedly exerts robust pharmacological actions via modulation of signaling pathways and targets (De Luca et al 2015).…”
Section: R a F Tmentioning
confidence: 99%
“…Cellular biosynthesis of taurine occurs in the liver via the cysteine sulfonic acid pathway while it is exogenously obtained from dietary sources (Huxtable 1992;De Luca et al 2015). Besides its nutraceutical role, taurine reportedly exerts robust pharmacological actions via modulation of signaling pathways and targets (De Luca et al 2015). Although no data on the systemic toxicity of taurine is available till date, 3 g per day of taurine for 4 months produced no obvious signs of toxicity during human trials (Shao and Hathcock 2008).…”
Section: R a F Tmentioning
confidence: 99%
“…Tau possesses anti-inflammatory and immune-regulatory properties [21]. In iron-potentiated alcoholic liver fibrotic rats, Tau restored mitochondrial function, prevented DNA damage and apoptosis.…”
Section: Introductionmentioning
confidence: 99%